An exploration of parents' and professionals' roles in sharing illness and treatment information with children who have cancer. (4th April 2011) - Kumpunen, S; Aldiss, S; Forbat, L; Goulden, N; Horstman, M; MacIntyre, V; Ranasinghe, N; Say, T; Gibson, F
Abstract : Background: Children aged 4–10 years with cancer rely on their parents for information. Inadequate and incomplete information about diagnosis and treatment increases children's worries and fears and compromises their abilities to participate more fully in their care and decision-making in later life. Aims: (1) To investigate the roles that parents and health professionals play in providing children (aged 4–10 years) with information about acute lymphoblastic leukaemia (ALL). (2) To develop and feasibility test an intervention to support parents in sharing information about ALL with their children. Methods: The two-phase study conducted interviews, online forums, and focus groups with 28 parents and 26 professionals over 12 months at one principal treatment centre in London. Grounded theory was used to code data, create concepts and theory. Guided by the MRC Framework for developing and evaluating complex interventions, 1 an information-sharing package was developed and feasibility tested. Analysis: Data analysis revealed that professionals in specialist areas shared medical information with families primarily at diagnosis, with little formal follow-up. No systematic communication 'protocol' existed to review basic concepts of leukaemia throughout treatment; informal assumptions were made between health professionals about how to build on families' knowledge. Parents had no support in translating information to their child, but saw it as their role. Intervention: A multi-disciplinary analysis team created HELP (Harmonising Education on Leukaemia for Parents), an internet-based and leaflet information package to follow the treatment phases of the MRC UKALL2010 protocol and consolidate information about medical and non-medical issues (eg, procedures, return to school), encourage family discussion, and suggest key questions for families to ask professionals. HELP aims to increase parents' self-efficacy of sharing information with their child, and in the long-term, to prepare children to become active participants in healthcare and decision-making. Conclusion: Parents expressed the need for more support in providing information to their children. Formal evaluation of the effectiveness of HELP in affecting parents' and children's knowledge, parents' self-efficacy and anxiety, children's behaviour and coping is required. Evaluation would add to the literature on communication interventions in children's cancer care, which lack an exploration of parents' significant communication and information-sharing roles.